Extra-soft red copper strip and grain refinement production process thereof
By combining low-temperature hot rolling and stepped heat treatment annealing with high-temperature short-time annealing, the problems of coarse grains and uneven microstructure in copper strip were solved, achieving fine grain softening and high conductivity, thus meeting the application requirements of extra-soft copper.
Patent Information
- Application Number
- CN202610198349.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-11
- Publication Date
- 2026-03-17
- Estimated Expiration
- 2046-02-11
AI Technical Summary
Existing technologies struggle to achieve grain refinement and ensure uniform microstructure while maintaining the high purity, high conductivity, and ultra-soft state of copper. This results in insufficient material strength and fatigue resistance, as well as surface quality issues during subsequent processing.
The process employs a combination of low-temperature hot rolling and stepped heat treatment annealing and high-temperature short-time annealing. The low-temperature hot rolling introduces uniform deformation energy storage, the stepped annealing forms fine and uniform recrystallization nuclei, and the high-temperature short-time annealing achieves softening while avoiding excessive grain growth.
The average grain size of the copper strip was ≤30μm, Vickers hardness HV≤50, elongation after fracture A50≥45%, conductivity ≥100% IACS, and the grain size distribution was uniform, which improved the strength, fatigue resistance and surface quality of the material.
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of non-ferrous metal processing, and particularly relates to a super-soft red copper strip and a grain refinement production process thereof. BACKGROUND
[0002] High-purity red copper (such as T2, TU1 and TU2) is widely used in the fields of electronic components, power transmission, precision instruments, heat exchangers and the like due to its excellent electrical conductivity, thermal conductivity, corrosion resistance and non-magnetic property. Many application scenarios not only require the copper material to have a very high electrical conductivity (close to the theoretical value of pure copper), but also require the copper material to be in a super-soft state (Vickers hardness HV≤50) and have a very high ductility (elongation A50≥45%) so as to facilitate subsequent precision stamping and deep drawing.
[0003] In the traditional production process, in order to obtain the mechanical properties of the super-soft state, the production process mainly relies on final high-temperature long-time annealing. However, such an annealing process is prone to cause abnormal grain growth, forming coarse grains, and the average grain size is often greater than 50 μm or even 100 μm. The coarse grains can significantly reduce the strength and fatigue resistance of the material, and the surface "orange peel" phenomenon is easy to occur, which affects the surface quality of the product and the yield of the final product in the subsequent processing such as bending and stamping.
[0004] If cold deformation is introduced in the processing process to refine the grains, the strength can be improved, but the softness of the material will be sacrificed. Subsequently, higher temperature or longer time annealing is needed to soften, which further aggravates the problem of grain coarsening. Moreover, the coarse grain structure is often accompanied by non-uniformity of properties such as hardness and elongation in different parts of the material, which also leads to poor product reliability in the subsequent processing.
[0005] In the prior art, there are also methods such as intermediate annealing and adjusting the rolling passes, but it is still difficult to effectively refine the grain size to below 30 μm or even to the range of 15-25 μm while ensuring the super-soft state (HV≤50, A50≥45%) and maintaining good uniformity. Although the addition of trace grain refinement elements such as Ag, Fe and Zr can inhibit grain growth, it will significantly reduce the electrical conductivity, which does not meet the requirements of high-purity and high-conductivity red copper.
[0006] Therefore, it is of important industrial application value and urgent technical needs to develop a production process that can realize significant grain refinement and ensure uniformity of the structure while maintaining the high purity, high electrical conductivity and super-soft state of the red copper. SUMMARY
[0007] In order to solve the problems in the prior art, the application provides a special soft red copper strip and a grain refinement production process thereof, so as to solve the contradiction between grain refinement, high conductivity and special soft state of the special soft red copper strip in the prior art, and meet the application requirements of the special soft red copper strip.
[0008] In order to achieve the above-mentioned purpose, the technical scheme adopted by the application is as follows: a grain refinement production process of a special soft red copper strip, after the red copper cast blank is uniformly heated, low-temperature hot rolling is performed, after the hot-rolled strip blank is milled, roughed and trimmed, first heat treatment annealing is performed, and after cleaning and rolling to the thickness of the finished product, second heat treatment annealing is performed, so as to obtain a special soft red copper strip product. In the application, the temperature of the low-temperature hot rolling is 350-500 DEG C, and the final rolling temperature is not lower than 350 DEG C. The first heat treatment annealing adopts a stepwise temperature rising and holding annealing system, which comprises the following steps: In the first stage, the temperature is raised to 240-260 DEG C at a speed of 80-120 DEG C / h, and the temperature is held for 1-2 hours; in the second stage, the temperature is raised to 370-390 DEG C at a speed of 40-60 DEG C / h, and the temperature is held for 3-4 hours; and in the third stage, the temperature is lowered to 60 DEG C at a speed of 40-70 DEG C / h, and the furnace is discharged and air-cooled to room temperature. The second heat treatment annealing is performed in a gas cushion type bright annealing furnace, and a high-temperature heat treatment annealing system is adopted, the annealing process is 600-650 DEG C, and the speed of the strip is 10-20 m / min.
[0009] The application has the beneficial effects that the temperature range of the low-temperature hot rolling is higher than the static recrystallization temperature of the red copper, the rolling deformation process and the recrystallization process are partially superimposed, the grains generated are finer than those generated by the traditional hot rolling process (the final rolling temperature is higher than 600 DEG C), and the deformation energy storage is more uniformly distributed.
[0010] In the first heat treatment annealing, the first stage promotes the low-temperature recovery process and eliminates the micro internal stress, and a large number of fine and uniformly distributed recrystallization nuclei are formed by utilizing the slow grain boundary migration speed at this temperature; the second stage is beneficial to the recrystallization temperature of the red copper, so that the nuclei formed in the first stage can fully grow and complete the recrystallization process, and fine and uniform recrystallization grains are obtained by utilizing the relatively low temperature rising speed and holding temperature to control the grain growth speed; and the third stage is a cooling stage.
[0011] The second heat treatment annealing adopts a gas cushion type bright annealing furnace, which avoids the excessive grain growth caused by long-time holding, the heat treatment annealing in this stage is performed at a temperature sufficient to fully soften the material for a short time, so as to further reduce the dislocation density, so that the material reaches the special soft state, and the temperature and speed of the gas cushion furnace are matched, so that the grain growth of the strip after the finished product rolling is minimized. After being discharged, the strip can immediately enter the online cleaning process, so as to avoid the further grain growth caused by the slow cooling speed.
[0012] Furthermore, the homogenization heating temperature is 880℃-920℃, and the temperature is maintained for 4-5 hours.
[0013] Its beneficial effects are: homogenization heating before low-temperature hot rolling eliminates casting segregation, dissolves non-equilibrium phases, fully dissolves any trace impurities that may exist, and prevents them from precipitating and hindering recrystallization in subsequent processes, thus preparing a uniform structure for subsequent hot working.
[0014] Furthermore, the low-temperature hot rolling process involves 7-11 rolling passes, with a total deformation of 90%-95%.
[0015] Furthermore, both the first and second heat treatment annealing were carried out in a protective atmosphere of decomposed ammonia, which consisted of 75% nitrogen and 25% hydrogen by volume.
[0016] Furthermore, in the first heat treatment annealing, the first stage heating rate is 100℃ / h, the holding temperature is 250℃, and the holding time is 1-2 hours.
[0017] Furthermore, in the first heat treatment annealing, the second stage heating rate is 50℃ / h, the holding temperature is 380℃, and the holding time is 3-4 hours.
[0018] Furthermore, the raw material for the copper billet is cathode copper, wherein the total mass fraction of Cu+Ag is ≥99.95%, and the oxygen content is controlled to be ≤0.0010%, the sulfur content to be ≤0.0010%, and the phosphorus content to be ≤0.0030%.
[0019] Its beneficial effects are: strictly controlling the content of impurity elements and avoiding the influence of elements such as oxygen, sulfur, and phosphorus on subsequent processing performance.
[0020] Furthermore, the casting temperature of the copper billet is controlled at 1150-1180℃, the temperature difference between the inlet and outlet cooling water of the crystallizer is controlled within 8℃, and secondary cooling water is used.
[0021] Its beneficial effects are: introducing a higher dislocation density and finer initial dendrites into the as-cast structure.
[0022] Furthermore, the extra-soft copper strip produced by this invention has the following properties: average grain size ≤30μm; Vickers hardness HV≤50; elongation after fracture A50≥45%; conductivity ≥100% IACS; uniform grain size distribution, with no abnormally large grains.
[0023] This invention also proposes an extra-soft copper strip, which is produced by the production process described above.
[0024] The technical principle of this invention is as follows: This invention introduces uniform deformation energy storage through low-temperature rolling: rolling in the temperature range of 350-500℃ (final rolling ≥350℃) combines deformation and dynamic / subdynamic recrystallization to provide uniform driving force for subsequent annealing.
[0025] This invention employs a stepped heat treatment annealing + high-temperature heat treatment annealing strategy: in the low-temperature nucleation / recovery stage, grain boundary migration is suppressed and a large number of uniform crystal nuclei are formed; in the recrystallization stage, grain growth is controlled to obtain fine grains; and in the high-temperature short-time softening stage, a soft state is achieved while minimizing grain growth.
[0026] The beneficial effects obtained by this invention are as follows: By combining the process of "high temperature homogenization + temperature-controlled hot rolling + stepped heat treatment annealing + high temperature heat treatment annealing", the contradiction of "softening must lead to coarse grains" in the traditional process is broken: (1) The average grain size of the final product can be stably controlled within the range of ≤30μm, which is much smaller than the range of 50μm or even 100μm in the traditional annealing process; (2) While obtaining a fine grain structure, the Vickers hardness HV≤50 and the elongation after fracture A50≥45% are guaranteed, which fully meets the application requirements of extra soft copper; (3) No alloying elements are added in the process, maintaining the high purity of copper and the conductivity ≥100% IACS; (4) Abnormal grain growth is avoided, the grain size distribution is concentrated, the material properties are uniform and stable, and the fine grain structure improves the strength, fatigue resistance and surface quality and yield of the material in subsequent precision processing.
[0027] Therefore, the present invention achieves significant technical effects in terms of grain refinement, significant grain refinement, excellent soft-state properties, high conductivity, good microstructure uniformity, and improved product performance through the synergistic effect of multiple steps. Detailed Implementation
[0028] The present invention will be further described in detail below with reference to the embodiments, but this should not be construed as limiting the invention in any way.
[0029] Example 1: Production of 1.5mm thick extra-soft copper strip The first step, raw materials and casting: T2 cathode copper (Cu+Ag≥99.95 wt%) is selected, and the cathode copper oxygen content ≤0.0010%, sulfur content ≤0.0010%, and phosphorus content ≤0.0030%. Charcoal and graphite powder are used for covering, and smelting is carried out in a reducing atmosphere. Vertical continuous casting is used to produce a 230mm thick and 620mm wide billet. The decomposed ammonia consists of 75% nitrogen and 25% hydrogen by volume. The casting temperature of the copper billet is controlled at 1150-1180℃, and the temperature difference between the inlet and outlet of the cooling water in the crystallizer is controlled within 8℃. Secondary cooling water is used to introduce a high dislocation density and fine initial dendrite structure into the as-cast structure. The second step is homogenization heating: the billet is held at 880℃ for 5 hours, then air-cooled to 500℃ after being taken out of the furnace, and then transferred to hot rolling. The third step is hot rolling: nine rolling passes are performed, with the rolling pass distribution being 230mm -215mm -185mm -143mm -107mm -75mm -46mm -30mm -21mm -15mm, the total deformation is 93.4%, and the final rolling temperature is 396℃, resulting in a 15mm thick strip. The fourth step involves milling, initial rolling, and trimming the hot-rolled strip to produce 2.0mm thick rolled coils. These coils are then individually loaded into a bell-shaped furnace for stepped heat treatment annealing: the first stage involves heating at 100℃ / h to 250℃ and holding for 1 hour; the second stage involves heating at 50℃ / h to 380℃ and holding for 3 hours; and the third stage involves furnace cooling at 50℃ / h to 60℃ followed by air cooling. The fifth step involves cleaning the product after the fourth heat treatment and rolling it to a finished thickness of 1.5mm. Then, a second heat treatment annealing is performed using an air-cushion bright annealing furnace at 650℃ and a speed of 15m / min. After exiting the furnace, the product immediately enters an online cleaning process to prevent the grains from growing further due to slow cooling. Step 6: Sampling and testing performance and grain size: average grain size is 28μm; Vickers hardness (HV1) is 48.3; elongation after fracture (A50mm) is 46%; conductivity is 101.4% IACS; the grains are uniform and fine, with no coarse grains; the product passes the test and is then cut and packaged.
[0030] Example 2: Production of 0.8mm thick extra-soft copper strip The first step, raw materials and casting: T2 cathode copper (Cu+Ag≥99.95 wt%) is selected, and the cathode copper oxygen content ≤0.0010%, sulfur content ≤0.0010%, and phosphorus content ≤0.0030%. Charcoal and graphite powder are used for covering, and smelting is carried out in a reducing atmosphere. Vertical continuous casting is used to produce a 210mm thick and 620mm wide billet. The casting temperature of the copper billet is controlled at 1150-1180℃, and the temperature difference between the inlet and outlet of the cooling water in the crystallizer is controlled within 8℃. Secondary cooling water is used to introduce a high dislocation density and fine initial dendrite structure into the as-cast structure. The second step is to homogenize the heating: hold the billet at 900℃ for 4 hours, and then air cool it to 500℃ after it is taken out of the furnace. The third step is hot rolling: seven rolling passes are performed, with the rolling pass distribution being 210mm -194mm -156mm -116mm -76mm -43mm -25mm -15mm, the total deformation is 92.8%, and the final rolling temperature is 412℃, resulting in a 15mm thick strip. The fourth step involves milling, initial rolling, and trimming the hot-rolled strip to produce 1.3mm thick rolled coils. Multiple rolled coils are then loaded into a bell furnace for stepped heat treatment annealing: the first stage involves heating at 120℃ / h to 260℃ and holding for 1 hour; the second stage involves heating at 60℃ / h to 390℃ and holding for 3 hours; and the third stage involves furnace cooling at 40℃ / h to 60℃ followed by air cooling. The fifth step involves cleaning the product after the fourth heat treatment and rolling it to a finished thickness of 0.8mm. Then, a second heat treatment annealing is performed using an air-cushion bright annealing furnace at 630℃ and 10m / min. After exiting the furnace, the product immediately enters an online cleaning process to prevent the grains from growing further due to slow cooling. Step 6: Sampling and testing performance and grain size: average grain size is 27μm; Vickers hardness (HV0.5) is 46.7; elongation after fracture (A50mm) is 48%; conductivity is 101.1% IACS; the grains are uniform and fine, with no coarse grains; the product passes the test and is then cut and packaged.
[0031] Example 3: Production of 0.3mm thick extra-soft copper strip The first step, raw materials and casting: T2 cathode copper (Cu+Ag≥99.95 wt%) is selected, and the cathode copper oxygen content ≤0.0010%, sulfur content ≤0.0010%, and phosphorus content ≤0.0030%. Charcoal and graphite powder are used for covering, and smelting is carried out in a reducing atmosphere. Vertical continuous casting is used to produce a 230mm thick and 620mm wide billet. The casting temperature of the copper billet is controlled at 1150-1180℃, and the temperature difference between the inlet and outlet of the cooling water in the crystallizer is controlled within 8℃. Secondary cooling water is used to introduce a high dislocation density and fine initial dendrite structure into the as-cast structure. The second step is to homogenize the heating: hold the billet at 920℃ for 4 hours, and then air cool it to 450℃ after it is taken out of the furnace. The third step is hot rolling: 11 rolling passes are performed, with the rolling pass distribution being 230mm -215mm -183mm -155mm -125mm -98mm -75mm -57mm -42mm -30mm -21mm -15mm, the total deformation is 93.4%, and the final rolling temperature is 367℃, to obtain a 15mm thick strip. The fourth step involves milling, initial rolling, and trimming the hot-rolled strip to produce 0.5mm thick rolled coils. These coils are then individually loaded into a bell-shaped furnace for stepped heat treatment annealing: the first stage involves heating at 80℃ / h to 240℃ and holding for 2 hours; the second stage involves heating at 40℃ / h to 370℃ and holding for 4 hours; and the third stage involves furnace cooling at 70℃ / h to 60℃ followed by air cooling. The fifth step involves cleaning the product after the fourth heat treatment and rolling it to a finished thickness of 0.3mm. Then, a second heat treatment annealing is performed using an air-cushion bright annealing furnace at 600℃ and 20m / min. After exiting the furnace, the product immediately enters an online cleaning process to prevent the grains from growing further due to slow cooling. Step 6: Sampling and testing performance and grain size: average grain size is 29μm; Vickers hardness (HV0.1) is 48.3; elongation after fracture (A50mm) is 46%; conductivity is 101.2% IACS; the grains are uniform and fine, with no coarse grains; the product passes the test and is then cut and packaged.
[0032] In the above embodiments, both the first heat treatment annealing and the second heat treatment annealing are carried out in a protective atmosphere of decomposed ammonia, wherein the decomposed ammonia consists of 75% nitrogen and 25% hydrogen by volume.
[0033] The following comparative examples demonstrate the production of 1.5mm thick copper strip using a process different from that of the present invention.
[0034] Comparative Example 1 The first step, raw materials and casting: T2 cathode copper (Cu+Ag≥99.95wt%) was selected, covered with charcoal and graphite powder, and smelted in a reducing atmosphere. Vertical continuous casting was used to produce a 230mm thick and 620mm wide billet, which was cooled with secondary cooling water to obtain a fine dendritic structure. The second step is to homogenize the heating process: hold the billet at 890℃ for 4 hours. The third step is to directly roll the strip in 9 passes without air cooling after it comes out of the furnace. The rolling passes are distributed as follows: 230mm-215mm-185mm-143mm-107mm-75mm-46mm-30mm-21mm-15mm. The total deformation is 93.4%, and the final rolling temperature is 642℃, resulting in a 15mm thick strip. The fourth step involves milling, initial rolling, and trimming the hot-rolled strip to produce a 1.5mm thick rolled coil. This coil is then individually loaded into a bell furnace for conventional heat treatment annealing: the temperature is raised to 380℃ at 100℃ / h, held for 4 hours, and then furnace cooled to 60℃ at 50℃ / h before being removed from the furnace and air-cooled.
[0035] The fifth step is to clean the heat-treated product; Step 6: Sampling and testing performance and grain size: average grain size is 85 μm; Vickers hardness (HV1) is 58.4; elongation after fracture (A50mm) is 44%; electrical conductivity is 101.1% IACS; microstructure observation: complete recrystallization, with coarse grains present. The product performance does not meet the requirements of the extra-soft copper strip described in this invention.
[0036] Comparative Example 2 The first step, raw materials and casting: T2 cathode copper (Cu+Ag≥99.95wt%) was selected, covered with charcoal and graphite powder, and smelted in a reducing atmosphere. Vertical continuous casting was used to produce a 230mm thick and 620mm wide billet, which was cooled with secondary cooling water to obtain a fine dendritic structure. The second step is to homogenize the heating: hold the billet at 890℃ for 4 hours, and then air cool it to 500℃ after it is taken out of the furnace. The third step involves nine rolling passes, with the passing passes distributed as follows: 230mm - 215mm - 185mm - 143mm - 107mm - 75mm - 46mm - 30mm - 21mm - 15mm. The total deformation is 93.4%, and the final rolling temperature is 379℃, resulting in a 15mm thick strip. The fourth step involves milling, initial rolling, and trimming the hot-rolled strip to form a 2.0mm thick rolled coil. This coil is then individually loaded into a bell furnace for conventional heat treatment annealing: the temperature is raised to 380℃ at 100℃ / h, held for 4 hours, and then furnace cooled to 60℃ at 50℃ / h before being removed from the furnace and air-cooled.
[0037] The fifth step is to clean the heat-treated product and roll it to a finished thickness of 1.5mm. Then, perform a second heat treatment annealing. The annealing process is carried out in an air-cushion bright annealing furnace at 650℃ and 15m / min. Step 6: Sampling and testing performance and grain size: average grain size is 44μm; Vickers hardness (HV1) is 53.8; elongation after fracture (A50mm) is 40%; microstructure observation: relatively uniform, with few coarse grains. The product performance does not meet the requirements of the extra-soft copper strip described in this invention.
[0038] Comparative Example 3 The first step, raw materials and casting: T2 cathode copper (Cu+Ag≥99.95wt%) was selected, covered with charcoal and graphite powder, and smelted in a reducing atmosphere. Vertical continuous casting was used to produce a 230mm thick and 620mm wide billet, which was cooled with secondary cooling water to obtain a fine dendritic structure. The second step is to homogenize the heating process: hold the billet at 890℃ for 4 hours. The third step is to directly roll the strip in 9 passes without air cooling after it comes out of the furnace. The rolling passes are distributed as follows: 230mm-215mm-185mm-143mm-107mm-75mm-46mm-30mm-21mm-15mm. The total deformation is 93.4%, and the final rolling temperature is 642℃, resulting in a 15mm thick strip. The fourth step involves milling, initial rolling, and trimming the hot-rolled strip to form a 2.0mm thick rolled coil. This coil is then individually loaded into a bell furnace and subjected to the stepped heat treatment annealing method of this invention: the first stage involves heating at 100℃ / h to 250℃ and holding for 1 hour; the second stage involves heating at 50℃ / h to 380℃ and holding for 3 hours; and the third stage involves furnace cooling at 50℃ / h to 60℃ followed by air cooling after removal from the furnace. The fifth step is to clean the heat-treated product and roll it to a finished thickness of 1.5mm. Then, perform a second heat treatment annealing. The annealing process is carried out in an air-cushion bright annealing furnace at 650℃ and 15m / min. Step 6: Sampling and testing performance and grain size: average grain size is 38 μm; Vickers hardness (HV1) is 47.1; elongation after fracture (A50mm) is 48%; conductivity is 101.3% IACS; microstructure observation: relatively uniform, with few coarse grains. Although the product performance does not meet the requirements of the extra-soft copper strip described in this invention in some indicators, it can still be used in scenarios where grain size requirements are not strict and product performance requirements are not high.
[0039] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Those skilled in the art should understand that modifications or equivalent substitutions can be made to the specific implementation of the present invention with reference to the above embodiments. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention are within the protection scope of the pending claims.
Claims
1. A process for the grain refinement of very soft copper strip, characterised in that, The red copper cast blank is heated by homogenization, then low-temperature hot-rolled, milled, roughed and trimmed, and then annealed by first heat treatment, cleaned, rolled to the finished thickness, and then annealed by second heat treatment to obtain the extra-soft red copper strip product; The temperature of the low-temperature hot-rolling is 350-500 DEG C, and the final rolling temperature is not lower than 350 DEG C. The first heat treatment annealing adopts a stepwise temperature rising and holding annealing system, including: The first stage is to rise the temperature to 240-260 DEG C at a rate of 80-120 DEG C / h, and hold for 1-2 hours; the second stage is to rise the temperature to 370-390 DEG C at a rate of 40-60 DEG C / h, and hold for 3-4 hours; the third stage is to reduce the temperature to 60 DEG C at a rate of 40-70 DEG C / h, and air cool to room temperature after discharging; The second heat treatment annealing is carried out in a gas cushion bright annealing furnace, and adopts a high-temperature heat treatment annealing system, with an annealing process of 600-650 DEG C and a strip speed of 10-20 m / min.
2. The process for grain refinement of extra soft copper strip as claimed in claim 1 wherein, The homogenization heating temperature is 880-920 DEG C, and the holding time is 4-5 hours.
3. The process for grain refinement of extra soft copper strip as claimed in claim 1 wherein, The low-temperature hot-rolling is carried out for 7-11 times, and the total deformation is 90-95%.
4. The process for grain refinement of extra soft copper strip as claimed in claim 1 wherein, Both the first heat treatment annealing and the second heat treatment annealing are carried out in a decomposed ammonia protective atmosphere, which is composed of 75% nitrogen and 25% hydrogen by volume.
5. The process for grain refinement of extra soft copper strip as claimed in claim 1 wherein, In the first heat treatment annealing, the first stage rising rate is 100 DEG C / h, the holding temperature is 250 DEG C, and the holding time is 1-2 hours.
6. The process for grain refinement of extra soft copper strip as claimed in claim 1 wherein, In the first heat treatment annealing, the second stage rising rate is 50 DEG C / h, the holding temperature is 380 DEG C, and the holding time is 3-4 hours.
7. The process for grain refinement of extra soft copper strip as claimed in claim 1 wherein, The raw material of the red copper cast blank is cathode copper, with a total mass fraction of Cu+Ag ≥ 99.95%, and the oxygen content ≤ 0.0010%, the sulfur content ≤ 0.0010%, and the phosphorus content ≤ 0.0030%.
8. The process for grain refinement of extra soft copper strip as claimed in claim 7 wherein, The casting temperature of the red copper cast blank is controlled at 1150-1180 DEG C, the temperature difference of the cooling water inlet and outlet of the crystallizer is controlled within 8 DEG C, and secondary cooling water is used.
9. The process for grain refinement of extra soft copper strip as claimed in claim 1 wherein, The produced extra-soft red copper strip has the following properties: average grain size ≤ 30 μm; Vickers hardness HV ≤ 50, elongation A50 ≥ 45%; electrical conductivity ≥ 100% IACS; grain size distribution standard deviation is small, and there is no abnormal coarse grain.
10. A very soft copper strip characterized in that, Obtained by the production process of any one of claims 1-9.
Citation Information
Patent Citations
Cable copper strip and processing technique thereof
CN101264572A
Copper strip annealing process
CN110387516A
Red copper thick plate and preparation method thereof
CN119372511A
Red copper material and preparation method and application thereof
CN119410952A
Method for manufacturing copper alloy sheet material
JP2015187308A